2006
DOI: 10.1182/blood-2006-03-013334
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell thrombospondin-1 and heparin-binding domain lead to dendritic-cell phagocytic and tolerizing states

Abstract: Apoptotic cells were shown to induce dendritic cell immune tolerance. We applied a proteomic approach to identify molecules that are secreted from apoptotic monocytes, and thus may mediate engulfment and immune suppression. Supernatants of monocytes undergoing apoptosis were collected and compared using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and differentially expressed proteins were identified using tandem mass spectrometry. Thrombospondin-1 (TSP-1) and its cleaved 26-kDa hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 53 publications
(69 reference statements)
5
130
0
2
Order By: Relevance
“…High concentrations of HSP-27 (1000 ng/mL) might induce such elevated PD-L1 levels, thereby triggering increased apoptosis in MO?iDC differentiation cultures. Uptake of apoptotic cells inhibits MO?iDC differentiation and HSP-27-mediated increased apoptosis could be a mechanism of HSP-27 inhibitory activity [40,41]. rhHSP-27 induced some apoptosis in MO?iDC differentiation culture at the concentration of 1000 ng/mL (Fig.…”
Section: Hsp-27 Did Not Induce Apoptosis Nor Selectively Deplete Idc mentioning
confidence: 96%
“…High concentrations of HSP-27 (1000 ng/mL) might induce such elevated PD-L1 levels, thereby triggering increased apoptosis in MO?iDC differentiation cultures. Uptake of apoptotic cells inhibits MO?iDC differentiation and HSP-27-mediated increased apoptosis could be a mechanism of HSP-27 inhibitory activity [40,41]. rhHSP-27 induced some apoptosis in MO?iDC differentiation culture at the concentration of 1000 ng/mL (Fig.…”
Section: Hsp-27 Did Not Induce Apoptosis Nor Selectively Deplete Idc mentioning
confidence: 96%
“…Recently, thrombospondin-1, a calcium-binding protein released from the engulfing cell, was also identified as a protein that is synthesized de novo when apoptosis is induced in monocytes, and that tolerizes immature DCs. 48 Necrotic cells release massive amount of high mobility group box 1 (HMGB-1) protein, which incites inflammatory responses of macrophages through pathways mediated by Toll-like receptor 2 (TLR2) and TLR4. 8,52 Whether HMGB-1 protein is specifically released by necrotic cells but not by apoptotic or secondary necrotic cells remains controversial.…”
Section: Factors Released By Dying Cellsmentioning
confidence: 99%
“…Apoptotic cells were labeled with DiI as described elsewhere [5,6,18] and added to iDC at different ratios for 2 h on day 6 of culture, followed by iDC staining with DC-SIGN FITC. Interaction was assessed with the FACScan TM .…”
Section: Apoptotic Cell and Latex Bead Interaction With Idcmentioning
confidence: 99%
“…Stuart et al [4] demonstrated in mice that DC that ingest apoptotic cells have a diminished ability to produce IL-12 in response to external stimuli, a property that corresponds to a failure to upregulate CD86. Earlier, we were able to show the generation of tolerizing, monocyte-derived DC that express low CD86 and MHC class II, and upregulate CCR7, as a result of interaction with iC3b-opsonized apoptotic cells [5], or via interaction with thrombospondin-1 produced by apoptotic cell [6]. In the present work, we are interested in studying the generation of tolerizing DC in a systemic autoimmune disease characterized by dysregulation of peripheral tolerance.…”
Section: Introductionmentioning
confidence: 99%